Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (Tai) Terhadap Pemahaman Konsep Matematis Peserta Didik Kelas VII SMPN 13 Padang - Dian Mawarni (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding mathematical concepts is one of the basic abilities that must be mastered by students so that the goals of mathematics learning can be achieved. In fact, in class VII SMPN 13 Padang showed the understanding_of mathematical_concepts is still low. An alternative that can be used as a solution to overcome this problem is by applying the Team Assisted Individualization type cooperative learning model. Based on data analysis shows that understanding the mathematical concepts of0students who0learn0with0the0cooperative0learning0model0of the TAI type0is0better0than0understanding the mathematical concepts of students who learn with direct instruction.Keywords0– Understanding of0mathematical concepts, Team Assisted Individualization, Direct Instruction